Improving the population genetics toolbox for the study of the African malaria vector Anopheles nili: microsatellite mapping to chromosomes - (:unkn) unknown (My University, 2011)
Anopheles nili is a major vector of malaria in the humid savannas and forested areas of sub-Saharan Africa. Understanding the population genetic structure and evolutionary dynamics of this species is important for the development of an adequate and targeted malaria control strategy in Africa. Chromosomal inversions and microsatellite markers are commonly used for studying the population structure of malaria mosquitoes. Physical mapping of these markers onto the chromosomes further improves the toolbox, and allows inference on the demographic and evolutionary history of the target species.
Keywords: African Research